ANALISIS RASIO KEUANGAN (CAMEL) TERHADAP KINERJA KEUANGAN BPD DENGAN GCG SEBAGAI PEMODERASI PERIODE 2017 – 2019 (Studi Empiris Pada Bank Pembangunan Daerah di Indonesia Tahun 2017 – 2019) - Ande Larista Simatupang; Tri Jatmiko Wahyu Prabowo (Diponegoro Journal of Accounting, 2021)
This study aims to examine the influence of financial ratio (CAMEL), there are CAR, NPL, NIM, BOPO, and LDR., to the financial performance of regional banks in Indonesia  that measured by Return on Assets (ROA) and Good Corporate Governance as moderated variable, based on number of board of directors and commissioners.            This study used annual report of regional banks in the period 2017-2019. The total sample of this study were 26 regional banks after selected by purposive sampling method. The analysis technique used in this study is linear regression to examine the relationship between variables that one with the other variables.            The results of this study indicate that NPL and BOPO has negatively and significant impact on ROA. While the CAR, NIM, and LDR has positively and significant impact on ROA. The results of this study also indicate that the board of directors and commissioners as moderating variables were able to moderate the influence of NPL and NIM on financial performance. However, it is unable to moderate the influence of CAR, BOPO and LDR on Return on Assets.